A fluorescent histone deacetylase (HDAC) inhibitor for cellular imaging1. Issue 37 (7th May 2015) - Fleming, Cassandra L.; Ashton, Trent D.; Nowell, Cameron; Devlin, Mark; Natoli, Anthony; Schreuders, Jeannette; Pfeffer, Frederick M.
<x xml:space="preserve">Abstract</x> Fluorescent 4MS, has comparable HDAC and anticancer activity to scriptaid and allows visualisation of rapid cellular uptake and cytoplasmic localisation.